Prevalence of antibiotic resistance genes in mining-impacted farmland environments - Hai-Yan Zou; Fang-Zhou Gao; Liang-Ying He; Min Zhang; You-Sheng Liu; Jun Qi; Guang-Guo Ying (Ecotoxicology and Environmental Safety)
Mining activities produce large quantities of tailings and acid mine drainage, which contain varieties of heavy metals, thereby affecting the downstream farmland soils and crops. Heavy metals could induce antibiotic resistance through co-selection pressure. However, the profiles of antibiotic resistance genes (ARGs) in the mining-affected farmland soils and crops are still unclear. Here we investigated contents of heavy metals, ARG abundances, mobile genetic elements (MGEs), and microbial community in mining-affected farmland soils and vegetables from Shangba village (SB), in comparison to a nearby reference village Taiping (TP). Results showed that in SB group, except for Cr, other metals were all above the Chinese Standards. When compared with the reference group, higher ARG abundances were detected in mining-affected farmland soils and vegetables, with great proportions of genes resistant to sulfonamides, chloramphenicols and tetracyclines. In addition, positive correlations were found between the above three ARG classes and heavy metals concentrations (especially Cu, Pb and Zn). Spearman’s correlations revealed that there were positive correlations between sul1 and total nitrogen, as well as tetB/P and pH. Additionally, the Shannon index values were different for the samples from two villages (p < 0.05). Proteobacteria and Actinobacteria were dominant phyla in soil samples. Network analysis suggested that multiple genera (belonging to Proteobacteria and Actinobacteria) were positively associated with many ARGs (p < 0.05), implying they might be potential hosts for ARGs. To sum up, this study provided clear evidence that mining activities caused severe heavy metals pollution to the farmland, thus posing co-selection pressure on the persistence of ARGs in the affected farmland environments.